DOUBLE-LAYER MODEL OF THE SCALABLE DISTRIBUTED DECENTRALIZED LEDGER - Grybniak, Sergyi (Scientific Works of Vinnytsia National Technical University, 2024)
In spite of the wide application of the distributed decentralized ledgers, in particular, in the popular platforms Bitcoin and Etherium, they inherent major faults. Their main drawback is low speed of transactions processing. To eliminate this drawback, in the given research two-layer model of the distributed decentralized ledger is suggested, this enables not only to increase the speed of transactions processing but increase the scalability. Each of the model layers differs both in the functions, to be performed and in the principle of the network creation. First – it is a network, constructed on the architecture using the directed acyclic graph – DSGChain, which itself creates the blocks. The second – it is a network that is classic blockchain. In this network the formulation of consensus Proof of Stake for the validation and finalization of blocks occurs. Within the frame of the suggested model the method of DAG blocks arrangement has been developed. The given method is based on the introduced notion of the skeletal blocks. The method enables to reduce substantially the traffic between two networks. Method of the optimistic (probabilistic) consensus formation has been developed. Probabilistic consensus enables to reduce the time of blocks finalization. In the process of the coteries formation for PoS consensus new method of mixing on the base of Tent transformation is suggested to use, this method increases the level of ledger security on the whole. On the base of the suggested model its program realization has been created in the form of the Waterfall platform. Loading experiments with the testing network demonstrated that it provides the rate of transactions processing of more than 2000 tps at a high level of scalability. Thus, the combination of the blockchain technologies and DAGChain in one model of the distributed ledger enables to increase the rate of transactions processing by orders. Further direction of the data processing acceleration is the application of sharding in DAGChain network, this can improve the efficiency indices of the distributed ledger.